2020
DOI: 10.1186/s40694-020-00093-1
|View full text |Cite
|
Sign up to set email alerts
|

Promoter tools for further development of Aspergillus oryzae as a platform for fungal secondary metabolite production

Abstract: Background: The filamentous fungus Aspergillus oryzae is widely used for secondary metabolite production by heterologous expression; thus, a wide variety of promoter tools is necessary to broaden the application of this species. Here we built a procedure to survey A. flavus genes constitutively highly expressed in 83 transcriptome datasets obtained under various conditions affecting secondary metabolite production, to find promoters useful for heterologous expression of genes in A. oryzae. Results:To test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Several recent efforts have used RNA-seq data to survey microbial genomes for constitutively, strongly expressed genes and test their upstream regions as potential drivers of heterologous gene expression in a biomolecule production platform. These approaches identified novel and strong promoter candidates; however, many of the sequences reported encompass the entire upstream window between the translation start site and the next upstream gene. Though using a large upstream window ensures that the sequence contains the promoter elements involved in transcription initiation, these regions may also contain other regulatory signals that, if incorporated in a heterologous expression cassette, may result in unanticipated expression effects.…”
mentioning
confidence: 99%
“…Several recent efforts have used RNA-seq data to survey microbial genomes for constitutively, strongly expressed genes and test their upstream regions as potential drivers of heterologous gene expression in a biomolecule production platform. These approaches identified novel and strong promoter candidates; however, many of the sequences reported encompass the entire upstream window between the translation start site and the next upstream gene. Though using a large upstream window ensures that the sequence contains the promoter elements involved in transcription initiation, these regions may also contain other regulatory signals that, if incorporated in a heterologous expression cassette, may result in unanticipated expression effects.…”
mentioning
confidence: 99%
“…However, recently it has been shown that dikaritin precursor peptides share their architecture not only between themselves but also with a much larger group of peptides called Kex2-processed repeat proteins (KEPs), most of which are not RiPPs. 51,52 Consequently, genome mining for dikaritins based solely on the characteristics of the precursor peptide will yield both dikaritins and KEPs, 52 which leads to the question of what biosynthetic features separate the two. A recent survey of 1461 fungal strains for KEPs suggested a potential evolutionary relationship between larger linear KEP-derived peptides with various biological functions (including yeast a-mating factor) and KEP-derived RiPPs.…”
Section: Borosins (Omphalotins)mentioning
confidence: 99%
“…For example, the OA-regulatable promoters can be used for the identification of oleate response elements (ORE), which participate in oleate induction [30]. In this regard, promoter tools have been described in other filamentous fungi such as Trichoderma reesei, Aspergillus spp., and Penicillium chrysogenum, which are also used for the production of industrially relevant metabolites [31][32][33][34], highlighting the importance of the identification of native promoters that can be used for the development of efficient expression platforms.…”
Section: In Vivo Analysis Of New Promoter Sequencesmentioning
confidence: 99%